Monthly Variations of the Winter Precipitation over the Philippines During the Mature Phase of Eastern Pacific El Niño - Liao, Wenxu; Fan, Yi; Zhu, Shoupeng; Huang, Yanyan; Lv, Yang (Frontiers in Earth Science, 2021)
The monthly variations of precipitation over the Philippines in winter during the mature phase of eastern Pacific El Niño is investigated with datasets of reanalysis and observations from 1979 to 2019. It is found that El Niño shows weak impact on the simultaneous December precipitation, whereas significant influence can be detected in January and February. In December during mature El Niño events, precipitation deficiency over the Philippines is not significant, while in January and February, precipitation decreases significantly over the southern Philippines as well as the areas to the south east of the Philippines. Besides, the correlation between the consecutive dry days over southeast Philippines and ENSO is significantly positive in January and February but not in December. The eastward propagation of El Niño related anomalous anticyclone over the western North Pacific (WNPAC) from December to February is responsible for the changed relationship between El Niño and precipitation. In December, the center of WNPAC is located to the southeast of the Indo-China Peninsula, leading to weak lower-level wind anomalies and consequently, weak vertical movement and water vapor transport anomalies over the Philippines, which shows limited influence on the local precipitation. In contrast, the center of WNPAC is located to the southeast of the Philippines in January and February, and therefore the southern Philippines is occupied by anticyclonic water vapor transport as well as downward vertical motion, favoring less precipitations and larger than normal consecutive dry days.